The Effect of Firm Size, Investment Return, Claims Expense Ratio, and Volume of Capital on the Profitability of Sharia Insurance Companies - Shofiatul Munawaroh; Moh. Faizin (Universitas Islam Negeri Kiai Ageng Muhammad Besari Ponorogo, 2025)
Introduction: This study aims to examine how firm size, investment return, claims expense ratio, and capital volume influence the profitability of sharia insurance companies. Research Methods: The research method used in this study is a quantitative method, using panel data regression analysis. The number of samples studied is 10 sharia insurance companies and sharia business units registered with the Indonesian Sharia Insurance Association (AASI) that consistently reported positive profits and did not suffer losses during the 2019-2023 period. Results: Firm size has a partial effect on the profitability of sharia insurance companies. Investment return also has a partial effect on the profitability of these companies. The claims expense ratio, however, does not partially impact their profitability. Conversely, the capital volume does partially influence the profitability of sharia insurance companies. Together, firm size, investment return, claims expense ratio, and capital volume collectively affect the profitability of sharia insurance companies.